Sidang Isbat, Urgensi dan Dinamikanya - Fadholi, Ahmad (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2019)
Sidang Isbat is part of the government's efforts to provide legal certainty to the Indonesian commuunity about the time to start worship namely fasting during the month of Ramadhan. Sidang Isbat requires a good relationship between religion and the state in realizing the unity and integrity of the nation. Sidang Isbat minimizes the attitude of sentiment towards government decisions due to the representation of each group with a different perspective.